Application of Educational Psychology-Based Dance Therapy in College Students’ Life Education - Zhong, Haiyan; Zhao, Chunhui; Zhang, Fengrui; Zhang, Ruizhi (Frontiers in Psychology, 2022)
The purpose is to strengthen the life education of contemporary college students and give better play to the vital role of life education in preventing college students' mental diseases. Specifically, it discusses the role of Dance Therapy (DT) in College Students' Life Education (CSLE). Firstly, based on Educational Psychology (EP), this paper analyzes the relevant theoretical concepts of EP and life education and discusses the importance of life education to contemporary college students. Secondly, following a Questionnaire Survey (QS) and using Deep Learning (DL) Convolutional Neural Network (CNN) and Facial Emotion Recognition (FER), this paper reviews and examines the CSLE's current situation and the DT effect. Research findings are summarized combined with the QS results and scores of 20 subjects before and after five activities in three months. (I) After DT intervention, the positive dimensions of college students' life values have improved, especially self-development and dedication, and their quality of life is refined. Thus, DT group counseling proves the positive role of DT in CSLE. (II) After DT intervention, 96.5% of the members think DT is effective. Therefore, EP-based DT is more effective and scientific in CSLE. The research findings provide a DT-based teaching concept for CSLE, explore the feasibility and effectiveness of life education, and enrich the DT scheme of CSLE. The research provides a practical reference for further applying DT in college students' psychological education.